Long-term quality of life and sensory impact of great auricular nerve preservation in parotid surgery as measured with the Parotidectomy Outcome Inventory-8 - Bulut, Cem; Hohenberger, Ralph; Plinkert, Peter K.; Federspil, Philippe A. (Clinical otolaryngology, 2019)
Objectives This study aimed to evaluate sensory dysfunction resulting from great auricular nerve (GAN) sacrifice versus preservation in parotid surgery for benign lesions and its imact on long-term health-related quality of life (QOL). Design Retrospective. Setting/main outcome measures Participants were divided into two groups (GAN and non-GAN), and both short-term (two postoperative weeks) and long-term (at least 5 years) QOL were assessed. The second item of the Parotidectomy Outcome Inventory-8 (POI-8) was used to analyse postoperative sensory loss. All items of the POI-8 questionnaire were used to determine health-related QOL.We used t test for dependent samples and Mann-Whitney U-test to compare patient groups Participants A total of 137 patients (65 male and 72 female) enrolled in this study. Average age at the time of surgery was 53 years (±12.8). Results The GAN preservation group had significantly better sensation than the GAN sacrifice in short term (2.8 vs 2.1; P = 0.017). Both groups experienced improved sensation in the long term, and there was a trend towards better QOL in the GAN-preservation group. However, the difference in sensation was not statistically significant (1.7 vs 1.3; P = 0.145). Health-related QOL also increased in the long term (compared to short term) for both groups (7.6 ± 6.2 to 12 ± 7.6; P < 0.0001) postoperatively. GAN preservation did not significantly improve sensation in long term, nor did it increase health-related QOL postoperatively. Conclusion Although GAN preservation was easily feasible, it only improved sensation in short term. We report a negative result: GAN preservation did not significantly improve sensation in long-term, nor did it increase health-related QOL postoperatively when compared to GAN sacrifice.
Gesehen am 23.09.2019